Requiem pour Ongola en Camfranglais: Une Poetique Camerounaise - Vakunta, Peter W. (Book collections on Project MUSE., 2015)
"Using linguistic stylings as subversive as the messages nestled between the lines, Vakunta's Requiem for Ongola in Camfranglais: Cameroonian poetics presents a scathing critique of the corruption of democracy into "democraziness" running rampant in the "Sick Man of Africa". Written in Camfranglais, this is resistance poetry at its best: 'tokking' through the mouth of the voiceless", the author pulls no punches in condemning the country's roi faineant, the perverted acceptance of feymania, the reduction of the national Constitution into toilet paper, and the general climate of impunity that has created an atmosphere of frustration and hopelessness. Calling upon the redeeming power of the Word - "Speak truth!" - these verses deftly navigate through the multilingual lexicon of a new, African hybrid language, providing an insider's account of the real stakes at hand in Ongola, the Ewondo word for Yaounde."